4‐phenylpyridine suppresses UVB‐induced skin inflammation by targeting c‐Src in vitro and in vivo. Issue 14 (10th June 2022) - Kim, Ju Gyeong; Kang, Ha Yeong; Kim, Min Jeong; Lim, Seokwon; Lee, Chang Joo; Kim, Kyung‐Min; Jung, Sung Keun
Abstract: Acute or repetitive exposure to ultraviolet (UV) cause disruptions to the skin barrier and subsequent inflammatory skin disease. 4‐phenylpyridine (4‐PP) is a constituent of Brassica campestris L. ssp. Pekinensis and its effect on skin inflammation and molecular target remain unclear. The purpose of this study is to confirm the anti‐inflammatory efficacy of 4‐PP on UVB‐induced skin inflammation in human keratinocytes HaCaT and mouse skin and validation of its molecular target. 4‐PP also attenuated UVB‐induced phosphorylation of p38/mitogen‐activated protein kinase kinase (MKK) 3/6, c‐Jun N‐terminal kinase 1/2, MKK 4/7, extracellular‐signal‐regulated kinase 1/2, mitogen‐activated protein kinase 1/2. Additionally, 4‐PP inhibited UVB‐induced phosphorylation of epidermal growth factor receptor (EGFR) Y1068, Y1045 and 854 residues but not the proto‐oncogene tyrosine‐protein kinase c‐Src. Drug affinity responsive target stability assay revealed that 4‐PP directly binds to c‐Src and inhibits pronase c‐proteolysis. Knockdown of c‐Src inhibited UVB‐induced COX‐2 expression and phosphorylation of MAPKs and EGFR in HaCaT cells. Dorsal treatment of 4‐PP prevented UVB (0.5 J/cm 2 )‐induced skin thickness, phosphorylation of EGFR and COX‐2 expression in mouse skin. Our findings suggest that 4‐PP can be used as anti‐inflammatory agent with an effect of skin inflammation by inhibiting the COX‐2 expression via suppressing the c‐Src/EGFR/MAPKs signalling pathway.